Effects of a particle placed on the ossicles for microphoneless cochlear implant design - Kurt, Serkan; Ozsonmez, Ahmet G. (SAGE PUBLICATIONS LTD, 2021)
In a typical cochlear implant design, the ambient sound is detected via a microphone and the transmission unit of the implant is placed at the back of the auricle. However, this design has several drawbacks. Firstly, the subject cannot bath or swim comfortably with the microphone unit on, and secondly having an external attached unit which may be visible is cosmetically disturbing. Herein, the idea is to explore obtaining the acoustic signals that would directly drive the cochlear nerves, without using a microphone, in which only the vibrations of the ossicles are employed. Thus, the natural filter caused by the anatomy of the ear may be maintained. The proposed method is to place or attach a micro-electro-mechanical-system (MEMS) type of tiny and lightweight accelerometer to sense or detect the vibrations of ossicles, namely malleus, incus and stapes. A quick analysis or first-thought revealed that physically longer extension of the incus is the most suitable and/or convenient place to attach such a sensor. The model adopted has been optimized to match the amplitude and phase response of the human ear from a system analysis point of view. Some simulation experiments had been done to study and understand the possible loading effects of placing a sensor on the incus. Purpose of the simulations is testing the feasibility before the very difficult surgical procedures. Preliminary results indicate that placing a sensor of weight up to 36 mg does not seriously affect the amplitude and the phase response of the ear. This study is yet another example of how simulations of physiological systems can be advantageous and facilitating in the design of biomedical systems.
Keywords: Mathematical model of ear; cochlear implant; signal analysis; mechanical loading effect; micro-electro-mechanical-system; Engineering